2023
DOI: 10.34133/research.0052
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Phenolic Network-Facilitated “Foe-to-Friend” Conversion of Melittin for Cancer Immunotherapy with Boosted Abscopal Effect

Abstract: As a naturally occurring cytolytic peptide, melittin (Mel) has strong cytolytic activity and is a potent therapeutic peptide for cancer therapy. However, the serious hemolytic activity of Mel largely impedes its clinical applications. In this work, based on the strong interactions between proteins/peptides and polyphenols, we develop a tannic acid–Fe 3+ metal–phenolic network (MPN)-based strategy that can convert Mel from foe to friend via shielding its positive charges and reducing its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Host defense peptides are emerging type of antitumor immunotherapeutic agents due to their good immunomodulatory activities. 22 They are widely expressed in complex organisms and constitute the first line of defense against infection, which is often achieved by lytic activities and the direct clearance of microbial infections. Melittin, the main effective component of bee venom, is an amphiphilic peptide with 26 amino acid residues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Host defense peptides are emerging type of antitumor immunotherapeutic agents due to their good immunomodulatory activities. 22 They are widely expressed in complex organisms and constitute the first line of defense against infection, which is often achieved by lytic activities and the direct clearance of microbial infections. Melittin, the main effective component of bee venom, is an amphiphilic peptide with 26 amino acid residues.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These characteristics make it unsuitable for effective biomedical applications in vivo. There have been studies using EGCG chelate with a variety of metal ions to prepare nanoparticles for the treatment of diseases [ [33] , [34] , [35] , [36] , [37] ]. However, EGCG is mostly used as a delivery vector, and the synergistic therapeutic effect of EGCG in the system has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Mel can disrupt the integrity of phospholipid bilayers by producing transmembrane pores and thus directly cause cell death. 13–15 In addition, recent studies have shown that Mel can effectively activate antitumor immunity by promoting the release of tumor-associated antigens and the secretion of various cytokines. 16,17 Thus, Mel is considered as a promising anticancer agent.…”
Section: Introductionmentioning
confidence: 99%